Perencanaan Struktur dan Pola Ruang Kawasan Pemerintahan Tobadak berbasis Konsep Urban Resilience - Irfan, Muhammad; Wahyuni, Sri; Iqbal Kamaruddin (Prodi PWK Universitas Tadulako, 2025)
Central Mamuju Regency is currently aggressively carrying out sustainable regional development. The development aims at equitable distribution in the economic, social and environmental fields. As with developments in developing regions, the very rapid penetration of development always creates an urban paradox which in this case triggers a process of urbanization of the population from rural areas to cities. This planning aims to create a space capable of meeting and controlling the needs of the Tobadak Government Area both economically, socially and environmentally. The analysis techniques used include: SWOT analysis, AHP analysis, Spatial analysis and Space Syntax analysis. The data used are primary and secondary data obtained from government agencies as well as observation, documentation and interviews. The main results of this planning are the master plan, spatial structure and pattern planning as well as regional disaster mitigation based on the concept of sustainable and integrated development.